1983
DOI: 10.1007/bf01851117
|View full text |Cite
|
Sign up to set email alerts
|

The influence of non-coronary collateral blood supply on the electively arrested heart during ischemia and reperfusion

Abstract: To study the influence of non-coronary collateral blood circulation (NCCBC) on the integrity of the ischemic myocardium a right-sided thoracotomy was performed on 15 anesthetized dogs. Following a total cardiopulmonary bypass (CPB), ventricular fibrillation was induced, during which 2,000 ml calcium-free cardioplegic solution LK 352 was given at the aortic root over an 8-10 min period. Precautions were taken to prevent retrograde blood flow into the coronary system via the coronary sinus. After 90 min of ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The influence of noncoronary collateral flow [20,21] during cardioplegic arrest on the [Cl – ] and [K + ] decrease of the coronary sinus effluent cannot be ignored because the [Cl – ] and [K + ] of circuit blood were lower than those of the BCP solution. Although noncoronary collateral flow obviously affected our results, the relative contribution of the noncoronary collateral flow to the results of the present study could not be determined because the exact volume of noncoronary collateral flow circulating in the myocardium during cardioplegic arrest during aortic cross-clamping is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of noncoronary collateral flow [20,21] during cardioplegic arrest on the [Cl – ] and [K + ] decrease of the coronary sinus effluent cannot be ignored because the [Cl – ] and [K + ] of circuit blood were lower than those of the BCP solution. Although noncoronary collateral flow obviously affected our results, the relative contribution of the noncoronary collateral flow to the results of the present study could not be determined because the exact volume of noncoronary collateral flow circulating in the myocardium during cardioplegic arrest during aortic cross-clamping is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the increase in NCCMBF provided an alternative blood supply during myocardial ischemia. In myocardial biopsies from dogs subjected to cardiopulmonary bypass and cardioplegic arrest, the presence of erythrocyte-filled blood vessels pointed to the possibility of direct access of NCCMBF to the heart, despite correct aortic cross-clamping [ 55 ]. Notwithstanding the compensatory effect of NCCMBF in ischemic heart disease, its role in cardiac surgery may be detrimental.…”
Section: Observations From Clinical Practicementioning
confidence: 99%
“…Notwithstanding the compensatory effect of NCCMBF in ischemic heart disease, its role in cardiac surgery may be detrimental. Very few authors suggested that NCCMBF could reduce ischemic injury [ 55 ]. The majority believed NCCMBF could be detrimental because it can cause cardioplegic solution wash out, which in turn precipitates renewed electromechanical activity and the failure of perioperative heart protection [ 4 , 5 , 33, 34 ].…”
Section: Observations From Clinical Practicementioning
confidence: 99%